2019
DOI: 10.1103/physreve.100.032107
|View full text |Cite
|
Sign up to set email alerts
|

Stable adiabatic quantum batteries

Abstract: With the advent of quantum technologies comes the requirement of building quantum components able to store energy to be used whenever necessary, i.e. quantum batteries. In this paper we exploit an adiabatic protocol to ensure a stable charged state of a three-level quantum battery which allows to avoid the spontaneous discharging regime. We study the effects of the most relevant sources of noise on the charging process and, as an experimental proposal, we discuss superconducting transmon qubits. In addition we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 83 publications
(112 reference statements)
0
115
0
Order By: Relevance
“…This setup presents a number of benefits, not simultaneously met in any other battery-charger setup, such as no need of fine control over the preparation of the charged state and no necessity to exert any effort to maintain the battery in that state. Indeed, the existing setups either require isolating the system or engineering a 033413-9 special system-bath evolution [9,11,12] or maintaining fragile internal symmetries [13,14] or active external stabilization [16] to preserve the charged state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This setup presents a number of benefits, not simultaneously met in any other battery-charger setup, such as no need of fine control over the preparation of the charged state and no necessity to exert any effort to maintain the battery in that state. Indeed, the existing setups either require isolating the system or engineering a 033413-9 special system-bath evolution [9,11,12] or maintaining fragile internal symmetries [13,14] or active external stabilization [16] to preserve the charged state.…”
Section: Discussionmentioning
confidence: 99%
“…II and Appendix B), our device offers two main advantages: (i) the creation of the battery's charged state requires no fine external control and, since thermalization is the process preparing that state, is robust against minor variations of the system-bath interaction; (ii) it costs nothing to maintain the charged state for as long as might be needed-it is the stationary state of system-bath interaction. These advantages are not simultaneously met in other battery designs which either require finely tuned external fields to perform unitary charging operations on the depleted state of the battery and assume that the battery is isolated after it is charged [11,12]; or require system-bath interaction engineering [9]; or, to prevent the battery from leaking the charge, either rely on fragile symmetries of the system-bath interaction [13,14] or actively manipulate the battery [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the coupling between the charger and its external power supply necessarily introduces noise, which limits the charging process [36]. Recent proposals have shown how to mitigate the effect of environmental noise via measurements [37] or dark states [38,39], while other authors have instead suggested to harness noise as a charging mechanism [40][41][42][43][44][45]. These approaches are notable due to their stability, meaning that the battery's charge tends to a stationary value instead of oscillating over time [38,46].…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, quantum batteries (QBs) have been introduced [15,16] as small quantum systems able to temporarily store energy, to be used at a later stage. Different figures of merit, such as the charging time, the associated power, and the amount of JHEP11(2020)067 extractable work, have been analyzed [17][18][19][20][21][22][23] and bounds on their performances have been inspected, depending on the precise charging protocols [24][25][26][27][28]. These usually rely on an external charger, interacting with one or more cells of the QB [21,22,29], or on unitary (local or global) evolution of the closed system in a nonequilibrium setting, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after an initial growth, the average energy stored in a QB during the charging protocol inevitably undergoes fluctuations, which usually undermine its subsequent use. It is thus of great importance to find protocols able to stabilize energy storage [25,34] or, even better, systems which intrinsically suppress these unwanted fluctuations.…”
Section: Introductionmentioning
confidence: 99%